NIMG-53. GLUTAMATE/GABA RATIO ON MRS IS ELEVATED IN PATIENTS WITH LOWER GRADE GLIOMAS AND SEIZURES. (9th November 2020) - Rudà, Roberta; Pascuzzo, Riccardo; Mo, Francesca; Pellerino, Alessia; Barker, Peter B; Bizzi, Alberto; Soffietti, Riccardo
Abstract: BACKGROUND: There is lack of information on the role of excitatory and inhibitory neurotransmitters in the development of seizures in patients with lower grade gliomas. Increase of glutamate and downregulation of GABA have been suggested in preclinical models and human surgical samples to be associated with brain tumor-related epilepsy. MATERIAL AND METHODS: We prospectively investigated with the use of magnetic resonance spectroscopy (MRS) the differences in the ratio of metabolites (glutamate/GABA, glutamate/creatine and GABA/creatine) in the peritumoral areas between patients with or without seizures in a series of lower grade gliomas. Tumors were classified according to WHO Classification of 2016 as follows:11 grade II IDH mutated and 1p/19q codeleted; 3 grade III IDH mutated and 1p/19q codeleted; 6 grade II IDH mutated and 1p/19q intact; 1 grade III IDH mutated and 1p/19q intact; 1 grade II IDH wild-type. Patients received surgery alone or followed by temozolomide chemotherapy according to the presence of risk factors. RESULTS: At baseline evaluation, maximum glutamate/GABA values were significantly higher (p=0.023) in the peritumoral area of patients with seizures (1.008 ± 0.368) with respect to those without seizures (0.691 ± 0.170). No other metabolites ratio showed significant differences between the two groups. Similar results were obtained when analyzing the metabolites ratio in the examinations during the follow-up. In the cohort of patients with seizures (n.14) variations of metabolite ratios were not associated with tumor location, 1p/19q codeletion, use of AEDs, concomitant chemotherapy or seizure characteristics (type, duration, frequency). CONCLUSIONS: The study is ongoing with the aim of analyzing further the correlations between ratio of metabolites and status of the tumor (stable vs progressive).